A Comprehensive Study of Intermetallic Compounds in Solar Cell Interconnections and their Growth Kinetics. (November 2016) - Geipel, Torsten; Moeller, Monja; Kraft, Achim; Eitner, Ulrich
Abstract: Intermetallic compounds (IMC) in soldered interconnections influence the reliability of PV modules. Thus, the microstructure of solar cell interconnections and the growth of IMCs are to be investigated in this paper. Sn60Pb40 and Sn41Bi57Ag2 are chosen as alloy coatings of copper interconnectors and semi-automatically soldered to screen-printed front Ag-busbars of industrial mono-crystalline solar cells. The microstructure of the solder bonds is characterized with metallographic cross sections and confocal laser microscopy, as well as scanning electron microscopy and electron dispersive x-ray spectroscopy. The cross section samples are isothermally aged between 85 °C to 150 °C and for 15 hour to 155 hour to obtain the kinetic parameters of a diffusion-based growth model of the IMCs. The model is used to estimate the IMC thickness after 3000 h at 85 °C, and after 600 thermal cycles as well as after 25 years in the outdoor location Freiburg, Germany. It is found that extensive microstructural changes take place within the solder bonds during thermal aging. Grain coarsening within the solder matrix, in particular for Sn41Bi57Ag2 solders, is observed, which can lead to an entire Sn depletion of the solder matrix. Moreover, non-uniform Sn penetration and IMC growth at cavities and lead-glass particles of the busbar are observed for both solders, which is discussed in terms of its effect on metallization adhesion. Eventually, simulating the IMC growth for 3000 h at 85 °C forecasts a 3.7 μm thick Ag3Sn IMC at the busbar for the Sn41Bi57Ag2 solder compared to 2.6 μm for Sn60Pb40. The prognosis of the IMC thickness after 25 years in Freiburg yields an Ag3 Sn thickness of 1.3 μm for Sn41Bi57Ag2.